Influência do diazepam nos níveis dos bioindicadores de exposição ocupacional ao tolueno - Silveira, Alberto Thalison (2016)
Toluene (TOL) is an aromatic hydrocarbon widely used in glues, paints, detergents, dyes, gasoline, thinners and pharmaceuticals. Human exposure to TOL occurs through inhalation or skin contact, in the workplace, or as a drug of abuse. It has been reported that some drugs, such as ethanol and phenobarbital, can influence the kinetics of TOL metabolism due the interactions on cytochrome P450 (CYP) isozymes. Benzodiazepines (BZD) are drugs widely used and there is no information on the influence of this class of drugs on the eliminations of volatile organic solvents (VOS) in the labor environment. So, in the present study, we investigated the influence of diazepam (DZP) on the excretion of TOL by determination of their metabolites, hippuric acid (HA) and ortho-cresol (o-C). Male Wistar rats (n = 5 per group), 250 ± 10 g, were exposed to TOL at a concentration of 20 ppm in a nose-only exposure chamber (6h/day, 5 day/week, for 6 weeks) with simultaneous administration of DZP (10 mg Kg-1/day) (GTOL/DZP). A group treated under the same condition, but without DZP (GTOL), and a group exposed to air and treated with DZP (10 mg Kg-¹/day) (GDZP) were executed. The control group (CTRL) was exposed to air only. The urine excreted during the 16 h after the last exposure was collected and stored until the analysis. The urinary o-C levels were determined by liquid-liquid extraction (LLE), followed by separation and detection in a gas chromatography coupled to mass spectrometer (GC-MS), while, with a simple dilution of the collected urine in ultrapure water (1:10, v/v), HA and creatinine (CR) could be determined by high-performance liquid chromatography coupled to the photodiode array detector (HPLC-DAD). Blood collection occurred after 16 hours of the last administration of DZP. The plasma concentrations of DZP and its metabolite, nordiazepam (NOR), were analyzed by HPLC-DAD with prior sample preparation by LLE. All analytical methods used in this study were satisfactorily validated (r¹ > 0.99; accuracy and precision with relative standard deviation and relative error, respectively, less than 15%). After statistical processing of data it was possible to observe that there is influence of DZP on the excretion of o-C (p < 0.05, Mann-Whitney test) on the GTOL/DZP group, when compared to the GTOL group. The results permitted to conclude that the use of DZP seems to influence the excretion of TOL through the urinary o-C and this is a relevant information to be used in the biological monitoring of this solvent.